Design a Visually Impaired Walker Using an Internet of Thing -Based Smart Bracelet - Adjie Mazhari; Nina Paramytha (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The eyes are one of the most important senses in the human body. They are used to understanding the surrounding situation so people can understand what is around them. Visual impairment is divided into two types, total blindness and low vision, depending on the degree of disability. A standard walker is a stick that helps you assess the condition of the road and the obstacles in front of you. The developing electric mobility aids are not only walking sticks. A glove-shaped walker was developed to detect objects before the tent and provide information from beeps and vibrations. Produce a walker using a visually impaired smart bracelet using sensor technology to help the blind's vigilance and mobility capable of detecting objects at a predetermined distance. The tool successfully outputs information in human voices recorded in DFPlayer Mini according to the conditions of ultrasonic sensor readings and monitoring of smart bracelets through the blynk application. Operation There are buttons used to turn the system on and off. All sensor inputs and outputs will be processed using the ESP-8266 NodeMCU. From the test results of the entire system, it can be concluded that the smart bracelet runs optimally according to the block diagram the author has compiled. Write down the conclusions of your paper and further research suggestions in the form of narratives and not in bullet or numeral form.